Contested Land Rights and the Failure of Land Governance: Exploring Pathways to Resolution - Al-Ahyani, M. Zuhri; Effendi, Ghina Nabilah; Malik, Abdul; Deswita, Deswita; Rahmat, Al Fauzi (Jambe Law Journal, 2026)
This study examines land manipulation and land disputes between a corporation and the local people in West Tanjung Jabung Regency, Jambi, resulting in the loss of a legitimate land entitlement. The conflict reflects broader agrarian challenges in Indonesia, including overlapping land claims and weak administrative governance, as well as unequal power relations between plantation companies and local communities. Using NVivo 15 Plus, the study analyzes data from legal documents, government regulations, and media reports using word frequency and crosstabs analyses. Mediation accounted for 60% of dispute resolution efforts, whereas litigation and arbitration each represented 20%. The findings reveal that the Village Cooperative Units (KUD) rejected the Corporate Social Responsibility (CSR) scheme as a settlement mechanism because it lacks legal authority to substitute land ownership rights under Indonesia’s Basic Agrarian Law. The study concludes that land restitution through independent audits, the application of the enclave principle under Government Regulation concerning the Resolution of Inconsistencies in Spatial Planning, Forest Areas, Licenses, and/or Land Rights, and multi-stakeholder oversight provides the most legally sound and socially just solution. Accordingly, the study offers a key contribution by proposing a collaborative land restitution model integrating administrative legal mechanisms, local government intervention, corporate accountability, and community participation to strengthen the governance of cultivation rights (HGU) and resolve plantation land conflicts.